2004
DOI: 10.3354/meps269209
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance and recruitment: a test of solute and substrate specificity using Mercenaria mercenaria and Capitella sp. 1

Abstract: Disturbances alter sediment surface chemistry, and this alteration promotes rejection of habitats by new benthic recruits. To date, the specific compound(s) affecting the rejection response have not been identified, but model predictions and experimental evidence suggest that oxygen and ammonium concentrations are informative. We evaluated the recruitment response of the opportunistic polychaete Capitella sp. 1 to disturbed, undisturbed and recovering sediments, with parallel measures of oxygen concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Ammonium concentrations in water samples taken above the test sediments both prior and subsequent to addition of new juveniles of both Arenicola and Mercenaria were relatively low (mean < 3.0 µM for "Medium" and < 8.4 µM for "High") and within the range of water column concentrations for the North Inlet (Marinelli and Woodin, 2004). This suggests the disturbance of porewater associated with the addition of new juveniles was minimal.…”
Section: B Sandwich Flume Experimentsmentioning
confidence: 73%
See 2 more Smart Citations
“…Ammonium concentrations in water samples taken above the test sediments both prior and subsequent to addition of new juveniles of both Arenicola and Mercenaria were relatively low (mean < 3.0 µM for "Medium" and < 8.4 µM for "High") and within the range of water column concentrations for the North Inlet (Marinelli and Woodin, 2004). This suggests the disturbance of porewater associated with the addition of new juveniles was minimal.…”
Section: B Sandwich Flume Experimentsmentioning
confidence: 73%
“…Other studies have found that exploratory time for Mercenaria on control sediment surfaces is longer on sediment surfaces that were disturbed, regardless of ammonium concentration (Marinelli and Woodin, 2004). It is possible that…”
Section: A Mercenaria Experimentsmentioning
confidence: 93%
See 1 more Smart Citation
“…In soft-sediment communities, local recruitment may be affected by grain size and sediment chemistry, which in turn can be influenced by resident organisms (e.g. Hockin 1982, Snelgrove & Butman 1994, Wu & Shin 1997, Marinelli & Woodin 2004, Beukema & Dekker 2005. Polluted sediments may affect settlement (Lenihan et al 2003, Stark et al 2004, Lu & Wu 2006, although it is difficult to distinguish this effect from early mortality.…”
Section: Introductionmentioning
confidence: 99%
“…I require specific sediment-bound chemical cues for settlement and metamorphosis. However, the precise nature of these settlement cues and the mechanisms involved in the larval settlement of this ecologically important species remain largely unknown (Marinelli & Woodin 2004).…”
Section: Introductionmentioning
confidence: 99%